Variabilidade morfológica e status taxonômico das amostras populacionais do gênero Clyomys (Rodentia: Echimyidae) - Bezerra, Alexandra Maria Ramos (2002)
The genus Clyomys has included two living species, C. laticeps (Thomas, 1909) and C. bishopi Avila-Pires & Wutke, 1981. The first nominal form would range from the Paraguayan Chaco to the states of Minas Gerais and Bahia throughout the Brazilian Cerrado, while the second is known only for regions of Cerrado enclaves of São Paulo state. The population of the Paraguayan Chaco was recognized as a subspecies of Clyomys laticeps on the basis of two individuals, and named C. laticeps whartoni Moojen, 1952. The samples from São Paulo were mainly distinguished by their larger body size and gray-yellowish coloration, in contrast to the smaller and predominantly rufous specimens of C. laticeps. The two species have revealed similar diploid numbers and chromosome morphology. The recent acquisition of larger series, representative of the two nominal forms, as well as the results of cytogenetic analyses of selected individuals prompted the question of the real divergence between the two recognized species, here examined in a more comprehensive analysis of the morphological variability of genus. Morphometric and qualitative analyses of skull morphology were confronted with the qualitative description of phallic morphology and pelage coloration, for a total of 112 specimens from 16 localities. The results indicate that: 1) criteria used to distinguish Clyomys bishopi are contestable, because presumptive diagnostic characters are shared with other populations from outside of São Paulo State; 2) no surveyed morphological character distinguishes the Paraguayan sample from Clyomys laticeps; 3) biogeographic history, associated with ecological restrictions imposed by the semifossorial habit of Clyomys may have contributed for the variability in bacular morphology and karyotype documented in extant populations; 4) variation in size may be related to climatic factors; 5) pelage coloration in Clyomys may have resulted from positive selection of individuals that displayed a more cryptic coloration in relation to the environment. Nevertheless, 6) a morphometric structuring of studied samples in two geographic groups was revealed. Additional karyological and genetic comparisons among different populations may provide a better framework for inferences on the taxonomical status of populational samples of Clyomys.